Teoria centrum-peryferii Immanuela Wallersteina i jej recepcja w archeologii. Studium przypadku: egejski system-świat w epoce brązu - Ciesielska, Adriana (Folia Praehistorica Posnaniensia, 2018)
This paper present the work of Nick Kardulias concerning the Egean World – System In the Bronze Age. It is paradoxical that the application of the Wallerstein’s model is the most popular and the most useful in Bronze Age studies. In the current article I assess the Kardulias’ work, his worldsystems approach to Aegean societies in the third and second millennia BC. He writes that ] in this era of the studied area societies developed complex economies based on accumulation of substantial agricultural surpluses, craft specialization, and intricate distribution systems.